Rebound with resilience : a mental resilience campaign for youth - Chu, Dennis Qi Xi (2019)
This paper presents Rebound with Resilience, a campaign aimed at cultivating resilience among secondary school students aged 13-17. Resilience refers to the ability to bounce back stronger from failure and adapt positively to stressors, a quality that is necessary in today’s unpredictable and changing landscape. To find out the current gaps and barriers to resilience, both primary and secondary research was done; secondary research involved understanding the cultural context and current efforts to build resilience, whereas primary research involved an extensive survey and focus groups with 4 schools and over 600 students. The research guided our campaign messaging, strategies and tactics. Our messaging was summarized in our 4 “Re” messages; namely “Reframe Perspective”, “Reclaim Control”, “Regain Confidence” and “Request Support”, each raising awareness and teaching specific factors that boost resilience. Theoretical frameworks of storytelling, positive psychology and experiential learning and gamification were used to inform our strategy and message delivery. These messages were communicated through a two-pronged offline and online strategies, where we engaged 6 schools and over 2000+ students to conduct assembly talks and experiential workshops. Our online content served to reinforce the messages and reach out to a wider target audience. After which, a post-test survey was done on the same students to ascertain a change in knowledge and attitudes. Lastly, key achievements and limitations of the campaign are discussed, along with future recommendations.